Efficacy of intravenous immunoglobulin treatment in children with common variable immunodeficiency - (:unkn) unknown (My University, 2011)
BACKGROUND: Children with common variable immunodeficiency (CVID) have increased susceptibility to infections. OBJECTIVE: We evaluated the role of intravenous immunoglobulin (IVIG) replacement therapy on the clinical outcome of patients with CVID. METHODS: We studied children diagnosed with CVID and treated with IVIG (500 mg/kg every 3 weeks). RESULTS: The study population comprised 29 children with CVID (mean SD] age, 11.8 6.1] years) with at least 1 year of follow-up before IVIG replacement therapy. Mean follow-up duration was 5.6 (3.5) years (range, 15 months-14 years). During therapy, median serum IgG levels increased from 410 to 900 mg/dL. The mean number of respiratory infections per patient per year decreased significantly from 10.2 to 2.5. The annual number and length of hospital stays decreased significantly from 1.36 to 0.21 and 16.35 to 6.33 days per patient, respectively. The mean annual number of antibiotics used decreased significantly from 8.27 to 2.50 per patient. Twelve patients had developed bronchiectasis before initiation of IVIG; 3 patients were cured of this condition. Age at diagnosis, diagnostic delay, number of respiratory tract infections, and number of antibiotics were found to be significantly higher in patients with bronchiectasis, as was lower B-cell percentage. However, gastrointestinal involvement due to noninfectious causes did not improve significantly after IVIG replacement therapy. CONCLUSION: CVID patients treated with IVIG (500 mg/kg every 3 weeks) had satisfactory serum IgG levels, fewer respiratory tract infections, fewer and shorter hospital stays, and reduced antibiotic usage. However, no effect on gastrointestinal involvement was observed. Early IVIG replacement therapy is important in preventing bronchiectasis.
Keywords: Female; Humans; Adolescent; Male; Child; Retrospective Studies; Child, Preschool; Anti-Bacterial Agents; Immunoglobulin G; Immunoglobulins, Intravenous; Respiratory Tract Infections; Length of Stay; Gastrointestinal Diseases; Common Variable Immunodeficiency